2023
DOI: 10.1007/s11032-022-01348-y
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of root sulfur metabolic pathway by overexpression of OAS-TL3 to increase total soybean seed protein content

Abstract: Sulfur is essential for plant growth, and the uptake of sulfate by plant roots is the primary source of plant sulfur. Previous studies have shown that the OAS-TL gene is a key enzyme in the sulfur metabolic pathway and regulates cysteine (Cys) synthase production. However, the interaction mechanism of the glycine max OAS-TL3 Cys synthase ( OAS-TL3 ) gene on soybean root morphology construction and seed protein accumulation is unclear. This study shows that mutant M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…More importantly, the fluorescence intensity of the meristematic zone was stronger than that of the elongation zone, which indicated that the content of Cys in the meristematic zone was higher than that in the elongation zone; this observation has not been reported to the best of our knowledge. These results are possibly attributed to the fact that O -acetylserine (thiol) lyase (OAS-TL), ,, which plays an important role in Cys synthesis in A. thaliana, existed in the mitochondria, and there are more cells in the meristematic zone, so the content of Cys in the meristematic zone was higher than that in the elongation zone.…”
Section: Resultsmentioning
confidence: 99%
“…More importantly, the fluorescence intensity of the meristematic zone was stronger than that of the elongation zone, which indicated that the content of Cys in the meristematic zone was higher than that in the elongation zone; this observation has not been reported to the best of our knowledge. These results are possibly attributed to the fact that O -acetylserine (thiol) lyase (OAS-TL), ,, which plays an important role in Cys synthesis in A. thaliana, existed in the mitochondria, and there are more cells in the meristematic zone, so the content of Cys in the meristematic zone was higher than that in the elongation zone.…”
Section: Resultsmentioning
confidence: 99%